Assessment of characteristics of acid mine drainage treated with fly ash - Shirin, S.; Jamal, A.; Emmanouil, C.; Yadav, A.K. (MDPI AG, 2021)
Acid mine drainage (AMD) occurs naturally in abandoned coal mines, and it contains hazardous toxic elements in varying concentrations. In the present research, AMD samples collected from an abandoned mine were treated with fly ash samples from four thermal power plants in Sin-grauli Coalfield in the proximate area, at optimized concentrations. The AMD samples were analyzed for physicochemical parameters and metal content before and after fly ash treatment. Morphological, geochemical and mineralogical characterization of the fly ash was performed using SEM, XRF and XRD. This laboratory-scale investigation indicated that fly ash had appreciable neutralization poten-tial, increasing AMD pH and decreasing elemental and sulfate concentrations. Therefore, fly ash may be effectively used for AMD neutralization, and its suitability for the management of coalfield AMD pits should be assessed further. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: abandoned mine; fly ash; acid mine drainag; SEM